Nanocomposites of cellulose-modified cerium oxide nanoparticles and their potential biomedical applications - Gusliani Eka Putri; Nurul Arifani; Tio Putra Wendari; Edi Syafri; R.A. Ilyas; Arniati Labanni; Syukri Arief (Case Studies in Chemical and Environmental Engineering)
Cellulose is a natural biopolymer extensively utilized in biomedical applications. This study aims to develop a novel cellulose nanofiber (CNF) from areca nut shell, reinforced with cerium oxide nanoparticles (CeO2NPs). XRD analysis confirms successful synthesis of crystalline CNF and CeO2NPs with the cubic structure, strengthened by Le-Bail refinement. Following FESEM and EDX analysis, spherical CeO2NPs nanoparticles with sizes ranging between 18 and 32 nm were formed and finely distributed on the CNF surface. The prepared CNF/CeO2NPs samples exhibited high antibacterial activity against S.aureus and E.coli. These findings highlight an innovative approach of materials with environmentally friendly for advanced biomedical applications.